2011
DOI: 10.1139/v11-021
|View full text |Cite
|
Sign up to set email alerts
|

Sensing hazardous metal ions using a fluoroionophore calix[4]arene species containing two 8-oxyquinoline groups

Abstract: The interaction of a calix [4]arene-based species containing two 8-oxyquinoline chromophore pendants with hazardous metal ions has been investigated using optical absorption and fluorimetric techniques. In the presence of Hg 2+ , Cd 2+ , and Pb 2+ ions, there is only a small decrease of the calixarene absorption band at 283 nm. The main changes are associated with the absorption band of the 8-oxyquinoline group at 315 nm, undergoing a systematic bathochromic shift to above 350 nm. In addition, a systematic dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 18 publications
(14 reference statements)
0
2
0
Order By: Relevance
“…23 The structure of the quinoline moiety is similar to that of the naphthyl unit, however only a few studies have been reported using quinoline as a fluorogenic unit in calixarene based fluoroionophores. [24][25][26][27] These quinoline containing systems have been reported for sensing of Cu 2+ and Eu 3+ , and also as redox switch as a data storage prototype, however no excimer formation is noted in these systems. [24][25][26] Recently, another calixarene based fluoroionophore with oxyquinoline as a fluorogenic unit has been reported for sensing of toxic metal ions such as Hg 2+ , Cd 2+ and Pb 2+ and weak excimer emission is noted upon addition of metal ions but no detailed discussion on it is reported.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…23 The structure of the quinoline moiety is similar to that of the naphthyl unit, however only a few studies have been reported using quinoline as a fluorogenic unit in calixarene based fluoroionophores. [24][25][26][27] These quinoline containing systems have been reported for sensing of Cu 2+ and Eu 3+ , and also as redox switch as a data storage prototype, however no excimer formation is noted in these systems. [24][25][26] Recently, another calixarene based fluoroionophore with oxyquinoline as a fluorogenic unit has been reported for sensing of toxic metal ions such as Hg 2+ , Cd 2+ and Pb 2+ and weak excimer emission is noted upon addition of metal ions but no detailed discussion on it is reported.…”
Section: Introductionmentioning
confidence: 99%
“…[24][25][26] Recently, another calixarene based fluoroionophore with oxyquinoline as a fluorogenic unit has been reported for sensing of toxic metal ions such as Hg 2+ , Cd 2+ and Pb 2+ and weak excimer emission is noted upon addition of metal ions but no detailed discussion on it is reported. 27 Quinoline based receptors of non-macrocyclic ligands, however, have been reported, which exhibited intra-and intermolecular excimer emission upon hydrogen bond mediated complexation with organic acids and phosphate anion. [28][29][30] With the aim to develop calixarene based chemosensors with excimer emission, we have synthesised a number of calix [4]arene derivatives with a quinoline moiety as a fluorophore.…”
Section: Introductionmentioning
confidence: 99%